2013
DOI: 10.1093/ndt/gft375
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease Improving Global Outcomes or creatinine kinetics criteria in acute kidney injury: a proof of concept study

Abstract: AKI classification proposed by a Cr kinetics model can be superior when diagnosing patients with previous CKD. However, KDIGO had a better performance in patients with no previous CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…The association of creatinine-based KDIGO criteria and kGFR with AKI and adverse events in a cohort of STEMI patients has been studied [21]. In contrast to our findings, the authors found superior sensitivity of KDIGO criteria in diagnosing AKI and predicting adverse outcomes compared with kGFR.…”
Section: Discussioncontrasting
confidence: 98%
“…The association of creatinine-based KDIGO criteria and kGFR with AKI and adverse events in a cohort of STEMI patients has been studied [21]. In contrast to our findings, the authors found superior sensitivity of KDIGO criteria in diagnosing AKI and predicting adverse outcomes compared with kGFR.…”
Section: Discussioncontrasting
confidence: 98%
“…Patients who do not meet RIFLE Risk stage criteria are included in KDIGO AKI stage 1. Thus, KDIGO classification is more sensitive to detect AKI [14]. Consequently, this increases the nephrotoxicity rate when KDIGO classification is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the 0.3-mg/dl absolute increase may not be appropriate to apply to those with elevated creatinine at baseline. Third, better use of readily available clinical data (such as those used by kinetic creatinine models [27,28] or integrating creatinine with other relevant laboratory values) may improve diagnostic and prognostic performance. Fourth, biomarkers with greater sensitivity and specificity than creatinine should continue to be developed, tested, and deployed.…”
Section: Discussionmentioning
confidence: 99%